Cognitive dysfunction in psychiatric patients: Comparison between schizophrenic and bipolar disorder patients with healthy subjects / Sylvia Wong Tyng Yng - Sylvia Wong, Tyng Yng (2017)
Background and Objective: The debate regarding the similarities and differences in cognitive functions in remitted schizophrenia and bipolar patients continues to be ongoing. This study was done to compare the level of cognitive functions as well as to determine associated factors influencing the cognitive functions of these patient populations with those of a healthy subject group. Methodology: This was a cross sectional study on stable schizophrenic and euthymic bipolar patients and healthy subjects. Subjects were included after screening through stringent inclusion and exclusion criteria, along with healthy subjects. The cognitive assessment tools used were the perceived deficits questionnaire (PDQ) (subjective assessment), the trail making tests (TMT), and the digit span. TMT A was to measure attention, TMT B and reverse Digit Span task measured executive functions, whereas the forward Digit Span task measured working memory. Results: Fifty-seven stable schizophrenic patients and forty euthymic bipolar patients as well as fifty-seven healthy subjects were included in the study. Stable schizophrenic patients did significantly poorly in all the objective tests (p<0.01) in comparison with the bipolar and healthy group. In the TMT A which measures attention, schizophrenic patients took 48.93 seconds on average, while on the TMT B, measuring executive function, they took 116.67 seconds. In comparison, the bipolar group spent 34.51 seconds on the TMT A, and 79.90 seconds on the TMT B. The healthy group used the least time to complete the tests, which was 23.98 seconds for the TMT A and 48.82 seconds in the TMT B. The bipolar group performed better than the schizophrenic vii group but fared worse than the healthy group in all the tests except the digit span forward test, which measures working memory (p=0.857). There were several demographic factors that were associated with poorer performance in the TMT and digit span tasks, namely more advanced age, Indian ethnicity, fewer years of education, being unemployed and longer duration of illness. After adjusting for those variables in multivariate analysis, the schizophrenia group performed significantly poorer than the healthy group in the TMT A and reverse digit span task (which measures executive function), and more advanced age and Indian ethnicity were independent risk factors for poorer performance in TMT A. The bipolar group performed significantly poorer than the healthy group in the TMT B and reverse digit span task. Indian ethnicity and less years of education were independent risk factors for poor performance in TMT A, and Chinese ethnicity performed better in the TMT B. Conclusion: Cognitive dysfunction was found to be present in stable schizophrenic and bipolar patients. In the schizophrenia group, the cognitive dysfunctions found were those of poor attention and executive function in comparison with the healthy group; while in the bipolar group, executive function was the main cognitive impairment in comparison with the healthy group. Thus assessment for cognitive dysfunction and measures to alleviate these symptoms should be included in the management of these patient groups.